Konsep Suaka Politik dalam Perspektif Fikih Siyasah - Iswandi Iswandi (TANFIDZIY, 2022)
human rights is a right owned by every human being in all parts of the world. Human rights have been owned by mankind since birth to the surface of the Earth, such as the right to life, religious rights and citizenship rights. All these rights cannot be taken away from humanity, even the whole world recognizes them. However, the reality that occurs in some countries there are still those who do not get human rights protection in their own country so they are forced to seek asylum in other countries. The method used in this study is a qualitative method. Sources of data are derived from primary data and secondary data obtained by tracing the literature related to the problems studied in this study. The nature of this research is included in the research that uses descriptive analytical method. The results of this study explain that every country is obliged to protect applicants for political asylum without distinction of Religion, Nation, tribe, race and group. The granting of asylum is based on humanitarian principles to protect human rights